Pengaruh Persepsi Harga, Kualitas Produk dan Promosi Terhadap Tingkat Kepuasan Konsumen Hp Xiaomi (Studi Kasus Pada Toko MI Shop di Kota Probolinggo) - Harvanto Harvanto; N. Rachma; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This research was conducted to determine the effect of price perception, product quality and promotion on the level of consumer satisfaction of Xiaomi mobile phones. This research was conducted in Probolinggo City, Mi Shop Shop Jl. Dr, Sutomo No.175, Mangunharjo, Kec, Mayangan, Probolinggo City, East Java. This type of research data is in the form of quantitative data, namely the data can be obtained through the distribution of questionnaires, interviews, observations, discussions or observations (surveys). This research is a research (explanatory research), and uses primary data sources, namely by distributing linkert-class questionnaires to consumers of the Probolinggo City Mi Shop Shop. The sample calculation in this study used the maholtra formula which resulted in 96 respondents. The results of this study are the variables of Price Perception, Product Quality, and Promotion have a simultaneous or partial effect on the Level of Consumer Satisfaction. Keywords: Price Perception, Product Quality, Promotion and Consumer Satisfaction